STRATEGI KOMUNIKASI DINAS PERHUBUNGAN KOTA PEKANBARU DALAM MENINGKATKAN PENERIMAAN RETRIBUSI PARKIR DI KOTA PEKANBARU - Wulandari, Tri; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The city of Pekanbaru is one of the fastest growing areas with a growing population every year. One of the great potentials that require special attention from the city government of Pekanbaru is the implementation of parking fees that are managed by the Transportation Office of Pekanbaru City based on the Regional Regulation of Pekanbaru City Number 3 of 2009. Within 3 years there has been an increase and decrease or instability in receipt of Parking Retribution. So that it can be concluded that there have been problems that have an impact on the unstable acceptance of parking fees annually. In this case the researcher focuses on the Communication Strategy of the Department of Transportation in increasing the receipt of parking fees. This study aims to determine the strategy of selecting communicators, audiences, messages and media from the Transportation Office of the City of PekanbaruThis research was conducted at the Transportation Office of the City of Pekanbaru. This study used a qualitative descriptive method, with purposive and snowball techniques. In this study 1 informant was chosen from the Head of the Parking UPTD, 1 informant from the TU Head of Parking Unit UPTD, 1 informant from the Head of Supervisory Team I of the UPTD Parking, 6 informants from the parking attendant and the community selected using accidental sampling. Data collection techniques used are interviews, observation and documentation Data analysis techniques are data reduction, data presentation, and conclusion. The technique of checking the validity of the data includes the extension of participation and triangulation.The results of the study indicate that the strategy of the Pekanbaru City Transportation Office in increasing the receipt of parking retribution is the communicator or resource person who conveyed the information is the integrated patrol member of the UPTD Parking who knows best and knows the conditions in the field and the behavior of illegal parking attendants. The target audience is the illegal parking attendant who was netted during the routine patrol of the Transportation Agency. The message delivered was persuasive and carried out directly. The media used are in the form of billboards, official websites and equipment from official parking attendantsKeyword: Communication Strategy, Departement Transportation, Parking Retribution